2012
DOI: 10.1007/s00167-012-1975-9
|View full text |Cite
|
Sign up to set email alerts
|

Close-looped graft suturing improves mechanical properties of interference screw fixation in ACL reconstruction

Abstract: Purpose In anterior cruciate ligament reconstruction with looped soft‐tissue grafts, an interference screw is frequently used for tibial fixation. This study compared three alternatives thought to improve the initial mechanical properties of direct bioabsorbable interference screw fixation: suturing the graft to close the loop, adding a supplementary staple, or increasing the oversize of the screw diameter relative to the bone tunnel from 1 to 2 mm. Methods Twenty‐eight porcine tibiae and porcine flexor digito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 37 publications
2
39
0
2
Order By: Relevance
“…5 We believe that the technique described is both easy to perform and highly feasible, reducing the risk of complications and technical problems that other systems entail. Table 1.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…5 We believe that the technique described is both easy to perform and highly feasible, reducing the risk of complications and technical problems that other systems entail. Table 1.…”
Section: Discussionmentioning
confidence: 95%
“…Fixation resistance has been proved to be increased if both ends of the graft are sutured beforehand. 5 The technique outlined in this report is designed to eliminate, or at the very least minimize, the risk of these complications arising, thus making reconstruction easier to carry out and achievable without specialized surgical instruments. It involves the use of the outsidein technique to create both the femoral and tibial tunnels, a procedure that can be performed with any of the ACL guides habitually used for the tibial tunnel, the only condition being that the guide must be adjustable to at least 80 .…”
mentioning
confidence: 99%
“…Therefore, the screw as an isolated fixation device may have been sufficient to bring the tendon to its plastic deformation, making additional attachments irrelevant from the mechanical standpoint. 10 , 12 However, another study observed a greater clinical stability in the group with additional fixation with staples two years after surgery. 9 …”
Section: Discussionmentioning
confidence: 97%
“…The staple can be used as a supplement to the interference screw, but only a few studies in the literature have assessed the mechanical behavior of the supplementary fixation with staples in the tibia. 7 , 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…form a closed loop. 5 A suspension device (G-Lok) is placed in position beforehand with a loop as long as necessary, depending on the graft's and tibial tunnel's lengths. This is accompanied by a further device of greater length (G-Lok XL; Stryker) to facilitate cortical fixation once the whole of the tunnel has been created with a diameter identical to that of the graft (Fig 3).…”
Section: Graft Harvesting and Preparationmentioning
confidence: 99%